Digital Technology Adoption in the Agriculture Sector: Challenges and Complexities in Africa - David Mhlanga; Emmanuel Ndhlovu (Human Behavior and Emerging Technologies)
This article examines the trends and rates of digital technological transformation in the African agricultural sector. While the literature on digital technologies in sectors such as manufacturing, communications, tourism and hospitality, and education abounds, focus on the applicability, relevance, and adoption of digital technologies in farming, particularly by smallholder farmers in agrarian Africa, remains limited. This is a problem that can have huge scholarly and policy implications and therefore needs to be addressed, at least at an academic level. This article uses a literature review to explore the level of digitalisation in African farming, examine the contribution of digitalisation to productivity and sustainability, identify the key challenges to and drivers for digitalisation in African farming, and propose policy frameworks to strengthen the digitalisation of agriculture. The analysis reveals that there are a number of significant challenges that need to be addressed. These include resource scarcity, limited expertise and training, a lack of digital infrastructure, data privacy and security concerns, and resistance by farmers. In spite of this, the agricultural sector in Africa has the potential to adopt technology and not only boost farm productivity but also engender sustainable and environmentally friendly farming. This, however, requires the collective effort of the public and private sectors as well as communities.